Lectures on solid state physics - Busch, Georg, 1908-; Schade, Horst, 1932- (International series in natural philosophy, 1976)
Lectures on Solid State Physics is a compilation of lectures concerned with various branches of solid state physics. It aims to develop basic physical ideas that lead to a better understanding of phenomena and effects. Comprised of 11 chapters, this book discusses several topics on solid state physics: structure of solids; interference effects in crystals; lattice dynamics; perfect and imperfect crystals; electrons and electron theory of metals; semiconductors; electrical contact effects; transport phenomena, and magnetism. Students, physics graduates, electrical engineers, chemists, and met.